On Farm Training and Demonstration of Covered Smut (Sphacelotheca Sorghi Clint) Management Technologies on Sorghum - Azanaw, Asfaw; Gelaye, Misganaw; Kefale, Yohannes (Asian Business Review, 2020)
Sorghum suffers from a lot of pests among which covered smut is the most important. Covered smut induced by the fungus Sporisorium sorghi and it is extremely seed-borne and seedling infection occurs at the time of germination and emergence of seedlings. The incidence of covered kernel smut varies from place to place, but in Ethiopia, it was estimated to be about 50%. This activity initiated to provide practical training on sorghum covered identification, monitoring, and technical skills to experts and farmers and to demonstrate the effect of seed dressing fungicides and traditional packages against sorghum covered smut. The field demonstration was laid out on a single plot with 4 treatments; Cow urine 1:1 (v/v) mixture, Thiram, Apron plus with 3g/kg, and Control untreated as a check. The plot size of the experiment was 10m x 10m with a plant spacing of 15cm and 75cm row spacing. Data on covered smut incidence and grain yield were recorded yield loss and partial budget analysis was made. Training of trainers on sorghum agronomic practices and diseases was given to 79 male and 37 female development agents for four woreda in central Gondar and development agents also gave training for 7925 male and 502 female farmers. There was no infestation of covered smut on fungicide dressed and cultural cow urine-soaked plots on both locations while an incidence of 2.8% at Gondar Zuria and 22.7% at Mirab Belesa. Relative yield advantage of the fungicides and cow urine is calculated over the control untreated check. Yield advantage of 20-26% on apron plus, 13-30% on Thiram, and 16-35% on cow urine were obtained over the untreated control check. Farmers have to use the nearby available cultural (cow urine) practice method and if not one of the available fungicides for control of covered kernel smut on sorghum production and should also be scaled out.